2020
DOI: 10.2351/1.5133158
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the effect of power and velocity of laser beam welding on the butt weld joint on TRIP steel

Abstract: In this study, the characterization of laser weld joint on transformation-induced plasticity (TRIP) steel sheets coupled with Nd:YAG laser welding was investigated, and the influence of welding conditions like angle of weld, power of laser, and welding speed on the strength of the joint was measured. The microstructure, tensile behavior, and microhardness of TRIP laser-welded sheets were examined in detail. The power was maintained constant, i.e., 1800 W, and by relatively varying the velocity from 25 to 30 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…In this paper, when laser power is from 2000 W to 2200 W, there shows a certain positive correlation trend among laser power, tensile strength and elongation. This correlation had been reported in the research of laser welded joint of high-strength TRIP steel by Rahul [18], and they found that as the laser power increased, the positive correlation between elongation and tensile strength became more obvious. In this case, the highest average tensile strength and average elongation of ASSAPH440/DC25D+ZF45 laser welded joint is 644.3 MPa and 23.9% respectively on the condition of 2000 W laser power, which is calculated by the minimum crosssectional area of the different thickness (2.0 mm+2.6 mm) dissimilar metal welded joint.…”
Section: Effect Of Laser Power On the Mechanical Properties Of Weldinsupporting
confidence: 69%
See 2 more Smart Citations
“…In this paper, when laser power is from 2000 W to 2200 W, there shows a certain positive correlation trend among laser power, tensile strength and elongation. This correlation had been reported in the research of laser welded joint of high-strength TRIP steel by Rahul [18], and they found that as the laser power increased, the positive correlation between elongation and tensile strength became more obvious. In this case, the highest average tensile strength and average elongation of ASSAPH440/DC25D+ZF45 laser welded joint is 644.3 MPa and 23.9% respectively on the condition of 2000 W laser power, which is calculated by the minimum crosssectional area of the different thickness (2.0 mm+2.6 mm) dissimilar metal welded joint.…”
Section: Effect Of Laser Power On the Mechanical Properties Of Weldinsupporting
confidence: 69%
“…So flow of shielding gas is also one of important parameters to welding quality. On the other hand, the composition of shielding gas has also a certain influence on surface quality of welding seam, penetration formation and mechanical properties of the welding joint [18,19]. The 99.9% purity argon shielding gas and 20 l min −1 shielding gas flow are determined in these welding experiments.…”
Section: Determination Of Welding Parameter Rangementioning
confidence: 99%
See 1 more Smart Citation
“…The weld was performed on the transverse direction of the length of the specimen, which is prepared as per the ASTM E8/E8M [40] standards with the desired length. The laser welding setup with a schematic diagram along with the chemical compositions and mechanical properties of as-prepared materials can be obtained from our recent publication [41].…”
Section: Methodsmentioning
confidence: 99%
“…AISI 2205 stainless steel sheets were joined using parameters given in Table 2 with TRUMPF LASER-CELL 1005 CO 2 laser beam welding machine in flat position and without additional welding wire. CO 2 laser beam welding technique differs from many traditional welding techniques because of low heat input, high focusing energy, high welding speed, narrow welding region, deep penetration, compatibility for automation, high mechanical strength, low distortion, and ability to weld without extra welding wire [4,11,[21][22][23][24][25].…”
Section: Experimental Studies Materials and Welding Processmentioning
confidence: 99%